2007
DOI: 10.1038/sj.hdy.6800978
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and the genetic structure of natural populations of Chamaecyparis obtusa: implications for management and conservation

Abstract: We investigated 25 natural populations of Chamaecyparis obtusa using 51 cleaved amplified polymorphic sequence (CAPS) markers, which were developed using information on sequence-tagged sites (STS) in Cryptomeria japonica. Most CAPS markers have codominant expression patterns, and are suitable for population studies because of their robustness and convenience. We estimated various genetic diversity parameters, including average heterozygosity (H e ) and allelic richness and found that the more peripheral popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…IBD was demonstrated in the C. japonica populations, especially among geographically close populations, but the IBD appears to be weaker in this species than in C. obtusa (Tsumura et al 2007). The genetic isolation of the Yakushima populations from the others contributed strongly to the IBD, but significant IBD was still detected when Yakushima populations were excluded.…”
Section: Resultsmentioning
confidence: 87%
“…IBD was demonstrated in the C. japonica populations, especially among geographically close populations, but the IBD appears to be weaker in this species than in C. obtusa (Tsumura et al 2007). The genetic isolation of the Yakushima populations from the others contributed strongly to the IBD, but significant IBD was still detected when Yakushima populations were excluded.…”
Section: Resultsmentioning
confidence: 87%
“…Since these populations are close to the Aso area where Nangouhi is used geographically, Nangouhi likely originated from one or more natural populations located somewhere in Kyushu; however, the suggestion that the source of a Nangouhi population be assigned to the Hikosan population needs careful scrutiny. Tsumura et al (2007) reported that the allele frequency of the Hikosan population was more similar to that of the Tanakamiyama population in Kinki compared to that of other populations in Kyushu. Nevertheless, hinoki populations tend to be clustered genetically within the same district or group of districts (see Fig.…”
Section: Genetic Origin Of Nangouhimentioning
confidence: 99%
“…1). Tsumura et al (2007) also argued that some individuals in the Hikosan population may have been introduced by humans.…”
Section: Genetic Origin Of Nangouhimentioning
confidence: 99%
See 2 more Smart Citations